Cultural Tourism and Cities: Kaunas Case - Kuizinaitė, Aurelija; Radzevičius, Martynas (Information & Media, 2020)
A feature of the modern society is the city which tries to express itself by means of social and physical environment. One of the means of expression are events whose activities engage local residents, visitors, guests, tourists, and, of course, distant spectators by means of smart global technologies. Cultural activities manifest by implementing cultural projects of various areas, starting from one-time local events, and ending with large-scale international projects. Cultural tourism is a great opportunity of urban and regional tourism development. Implementation of cultural events in cities can have impact on cultural tourism development and its planning, and can be one of the very important economic as well as sociocultural impact of tourism that manifests by created infrastructure, increasing supply of services and entertainment, and lively cultural life in cities. The work is relevant because it reveals for the first time how mega cultural events in cities are or can be an effect for cultural tourism development in cities.
Keywords: cultural tourism; city; impact; cultural tourism development; cultural tourism development planning